Arnold Toynbee and his Theory Challenge and Response in Interpreting History (Mutah Journal of Humanities and Social Sciences (MJHSS), 2023)
The main task of this research is to understand the philosophy of the famous British historian Arnold Toynbee in the interpretation, analysis, and criticism of history, based on his study, analysis and explanation of the general historical event in his famous book “A Study of History” in the light ofthe theoryof Challenge and Response, which is devoted to the interpretation of the historical event, and its understanding in the context of its general environment. Given the importance of the philosophical and methodological contribution that Toynbee made in this book in the field of theories and philosophies of the interpretation of general human history, his theory was considered a founding contribution to the philosophy and understanding of history, as well as one of the most important theories presented in modern times. No doubt it found those who support it at a time when it encountered criticism and opposition from others.This research includes a definition of Toynbee, his life, and his thoughts, in addition to elaboration of his methodology in the study of history, clarifying the theory of Challenge and Response and its position on the creation of civilizations, shedding light on the relationship between challenge and response and the growth as well as the collapse of civilizations and their degradation, and stretching the rhythm of decomposition to research, interpretation, and understanding. Another task for this research was to examine what was directed to Toynbee's philosophy in the interpretation of history, specifically to his theory in terms of criticism.
Keywords: Arnold Toynbee; challenge and response theory; interpretation of history